La cirugía centrada en la persona - Pacheco Ojeda, Luis (2018)
Context: person-centered medicine has been defined as "the medical practice that is based on the respect and follow-up of the patient's preferences, needs and values, elements that should guide all clinical decisions.Discussion: in response to medical paternalism, four basic principles have been proposed concerning the position of the doctor before his patient: autonomy, beneficence, non-maleficence and justice. The surgeon must use realistic criteria, based on reliable statistics and the best clinical evidence in order to recommend the best therapeutic decision, avoiding raising inappropriate optimism in the patient and their families. Sometimes,reaching this threshold of thought is difficult to obtain. Among the main current obstacles to a medicine centered on the person are at least two: the large volume of patients that a doctor has to attend, and the consequent stress for the doctor and the reduction of attention time.Conclusion: the relationship between patient, family members and surgeon must be the most diaphanous and affective to overcome the obstacles, pressures and concerns that currently surround the development of a surgical act.